Heat-physical problems of cryogenic corpuscular targets - Bukharov, A.V.; Ametistov, E.V.; Ginevsky, A.F.; Bukharova, M.A. (Вопросы атомной науки и техники, 2013)
In order to solve heat-physical problems in producing cryogenic corpuscular targets, the special mathematical model is developed. In developing mathematical model the following physical processes and the phenomena were considered: capillary disintegration of jets from the liquid cryogen, convective heat exchange with environment, acceleration of drops in a gas stream, radiation heat exchange, cooling and freezing of drops. The model allows to define the general parameters of cryogenic corpuscular targets (temperature, speed, deviation from vertical) since the moment of reception of monodisperse drops of liquid cryogenic agent till the moment of reception of solid granules. Results of calculations on offered mathematical model were used at creation of a prototype of a cryogenic corpuscular target for spectrometer PANDA. Work was supported by grant RFBR 12-08-01170-а and grant MPEI.